Blue-ribbon henry - Calhoun, Mary (New York Morrow Junior Books, 1999)
Although he feels insignificant next to the other animals at the county fair, Henry the car proves to be special in how own way.
D., unk., 2006
Keywords: Cats -- Fiction; Agricultural exhibitions -- Fiction